Lithium battery separator with uniform pore distribution and method of making same

CN116613466BActive Publication Date: 2026-10-30SINOMA LITHIUM BATTERY SEPARATOR CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310592512.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-24
Publication Date
2026-10-30
Estimated Expiration
2043-05-24

AI Technical Summary

Technical Problem

[0004]为解决现有技术中存在的静电纺丝法制备的隔膜机械强度较差以及孔洞分布不均匀的问题,本发明提供一种孔隙分布均匀的锂电池隔膜的制备方法

Benefits of technology

[0019]通过使用聚酰胺酸为原材料,原料耐高温、高孔隙率,存在大量极性基团的特点;聚酰胺酸亚酰胺化成聚酰亚胺,而聚酰亚胺具有高的机械强度、优异的抗拉、抗压强度,阻燃等特性,提升隔膜材料的强度,同时复合了聚乙烯吡咯烷酮以及制备好的均一尺寸的纳米ZIF-8材料,聚乙烯吡咯烷酮与ZIF-8之间通过氢键作用连接,在亚酰胺化过程中升温使得PVP骨架收缩形成孔结构,由于利用PVP和ZIF-8的限域作用,调控孔隙形貌,使孔隙更加均匀。同时制备的纳米级ZIF-8的引入可以进一步增加隔膜的热稳定性及吸液保液性能,提升了隔膜的浸润性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004246001510000051
    Figure BDA0004246001510000051
  • Figure BDA0004246001510000061
    Figure BDA0004246001510000061
  • Figure HDA0004246001520000011
    Figure HDA0004246001520000011
Patent Text Reader

Abstract

A lithium battery diaphragm with uniform pore distribution and a preparation method thereof, comprising the following steps: (1) taking polyvinylpyrrolidone, commercially available ZIF-8 nanoparticles with a particle size of about 40 nm, adding them into a polar organic solvent, uniformly mixing to prepare a mixed solution 1, adding commercially available polyamide acid, and continuously stirring to prepare a spinning solution; (2) electrospinning the spinning solution prepared in step (1) to prepare a diaphragm, drying the diaphragm, and heating at a rate of 1-5 ℃ / min to 230-300 ℃ and keeping for 1-2 h. The diaphragm prepared by the method has uniform pores, excellent thermal stability, liquid absorption and liquid retention performance, and advantages of high safety, flame retardation, good conductivity and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to membrane technology and materials in the field of new energy power and energy storage, specifically to a lithium battery separator with uniform pore distribution and its preparation method. Background Technology

[0002] Lithium-ion batteries primarily function by the shuttle of lithium ions between the positive and negative electrodes. During charging and discharging, lithium ions exchange by inserting and de-entering between the electrodes. The separator, one of the four crucial elements of a lithium-ion battery, exists between the positive and negative electrodes, separating the materials and preventing short circuits. The performance of the separator determines the battery interface properties, directly affecting the battery's capacity and safety. The quality of the separator significantly impacts the overall battery performance. Currently, polyolefin separators are the most widely used; however, polyolefin materials suffer from drawbacks such as high closed-cell temperature, poor wettability, and a large pore distribution.

[0003] As a crucial component of lithium-ion batteries, the separator needs to possess high lithium-ion conductivity, good chemical inertness, good mechanical properties, and a certain degree of thermal stability. During overcharging and over-discharging of lithium-ion batteries, the separator spontaneously shrinks to block electron migration, improving battery safety. Electrospinning is a common method for preparing lithium-ion battery separators. However, the main drawback of electrospinning is the poor mechanical strength of the resulting separator. Furthermore, the pore size and distribution rely heavily on the disordered arrangement of fibers and the properties of the raw materials themselves, resulting in poor pore uniformity and a higher shrinkage rate, which negatively impacts the separator's mechanical properties, stability, and cycle performance. Therefore, in the process of preparing lithium-ion battery separators using electrospinning, it is essential to achieve a separator with a uniform pore structure through specific methods. Summary of the Invention

[0004] To address the problems of poor mechanical strength and uneven pore distribution in the electrospinning method of existing technologies, this invention provides a method for preparing a lithium battery separator with uniform pore distribution.

[0005] The first objective of this invention is to provide a lithium battery separator with uniform pore distribution, the method comprising the following steps:

[0006] (1) Preparation of spinning solution: Polyvinylpyrrolidone (PVP) and ZIF-8 nanoparticles were added to a polar organic solvent and mixed evenly to prepare mixed solution 1. Polyamic acid was added and stirring was continued for 8 to 24 hours to prepare spinning solution.

[0007] (2) Preparation of sodium-ion battery coated separator: The spinning solution prepared in step (1) is electrospun to prepare a separator. After drying the separator, the temperature is increased at a rate of 1-5℃ / min to 230-300℃ and held for 1-2h.

[0008] During the pyrolysis process, due to the confinement effect, the PVP skeleton collapses less, and the micropores transform into mesopores, resulting in a more uniform porosity. In a specific embodiment, the polyvinylpyrrolidone (PVP) is K90.

[0009] Furthermore, the polar organic solvent in step (1) is N,N-dimethylformamide or N,N-dimethylacetamide.

[0010] Furthermore, the spinning solution in step (1) is used for subsequent operations after all bubbles have been eliminated; preferably, low-temperature settling is used to eliminate bubbles.

[0011] Furthermore, the volume / mass ratio of the polyamic acid solution to PVP in step (1) is 10:1 to 2:1.

[0012] Furthermore, the volume / mass ratio of polyamic acid to PVP in step (1) is 10:1, 10:3, or 5:1.

[0013] Furthermore, the mass ratio of polyvinylpyrrolidone (PVP) to ZIF-8 nanoparticles in step (1) is 5:1 to 1:1.

[0014] Furthermore, the mass ratio of polyvinylpyrrolidone (PVP) to ZIF-8 nanoparticles in step (1) is 3:1 to 1:1.

[0015] Furthermore, in step (2), the sample feeding speed of electrospinning is 0.1-1 mL / h, the voltage is 10-20 KV, and the receiving distance is 10-20 cm.

[0016] The second objective of this invention is to provide a lithium battery separator with uniform pore distribution, wherein the lithium battery separator with uniform pore distribution is prepared by the aforementioned preparation method.

[0017] A third objective of the present invention is to provide a lithium battery, wherein the lithium-ion battery includes the aforementioned lithium battery separator with uniform pore distribution.

[0018] The beneficial effects of this invention are as follows:

[0019] By using polyamic acid as a raw material, which is characterized by high temperature resistance, high porosity, and a large number of polar groups, the polyamic acid is imidized to form polyimide. Polyimide possesses high mechanical strength, excellent tensile and compressive strength, and flame retardant properties, thus improving the strength of the membrane material. Simultaneously, polyvinylpyrrolidone (PVP) and prepared uniformly sized nano-ZIF-8 materials are incorporated. PVP and ZIF-8 are linked by hydrogen bonds. During imidization, the increased temperature causes the PVP framework to shrink, forming a porous structure. The confinement effect of PVP and ZIF-8 regulates the pore morphology, resulting in more uniform pores. Furthermore, the introduction of the prepared nano-sized ZIF-8 further enhances the membrane's thermal stability and liquid absorption / retention properties, improving its wettability.

[0020] The diaphragm prepared by this invention has uniform pores, excellent mechanical strength, thermal stability and liquid absorption and retention performance, and the pore-closing temperature can reach below 130℃. It has advantages such as high safety, flame retardancy, good electrical conductivity and good liquid absorption and retention performance, which greatly expands the application range of the diaphragm. Attached Figure Description

[0021] Figure 1 Schematic diagram of lithium-ion battery separator fabrication by electrospinning;

[0022] Figure 2 Diagrams showing the pore size distribution of the diaphragm in Example 1 and Comparative Example 1. Detailed Implementation

[0023] The present invention will be further explained below with reference to the embodiments, but the embodiments do not limit the present invention in any way.

[0024] Test Performance Instruments and Methods

[0025] Example 1

[0026] This embodiment prepares a lithium-ion battery separator, and the preparation method is as follows:

[0027] (1) Preparation of spinning solution:

[0028] 2g of PVP (K90) and 1g of commercially available ZIF-8 nanoparticles with a particle size of approximately 40nm were added to 10mL of LDM solution under stirring. After mixing evenly, 10mL of commercially available polyamic acid (PAA) was added, and stirring was continued for 12h. The spinning solution was then placed in a refrigerator and allowed to stand for 12h.

[0029] (2) Preparation of the diaphragm: The prepared spinning solution was electrospun at an injection rate of 0.5 mL / min and a voltage of 14 kV, and the distance between the needle and the receiving device was adjusted to 10 cm. The spun diaphragm was dried in an oven at 105 ℃ for 12 h, and then placed in a muffle furnace and heated to 250 ℃ at a rate of 1 ℃ / min and held for 1 h.

[0030] Example 2

[0031] This embodiment prepares a lithium-ion battery separator, and the preparation method is as follows:

[0032] (1) Preparation of spinning solution:

[0033] 1g of PVP (K90) and 1g of commercially available ZIF-8 nanoparticles with a particle size of approximately 40nm were added to 10mL of LDM solution under stirring. After mixing evenly, 10mL of commercially available polyamic acid (PAA) was added, and stirring was continued for 12h. The spinning solution was then placed in a refrigerator and allowed to stand for 12h.

[0034] (2) Preparation of the diaphragm:

[0035] The prepared spinning solution was electrospun at an injection rate of 0.5 mL / min and a voltage of 14 kV, with the distance between the needle and the receiving device adjusted to 10 cm. The spun diaphragm was dried in an oven at 105 °C for 12 h, and then placed in a muffle furnace and heated to 250 °C at a rate of 1 °C / min and held for 1 h.

[0036] Example 3

[0037] This embodiment prepares a lithium-ion battery separator, and the preparation method is as follows:

[0038] (1) Preparation of spinning solution:

[0039] 3g of PVP (K90) and 1g of commercially available ZIF-8 nanoparticles with a particle size of approximately 40nm were added to 10mL of LDM solution under stirring. After mixing evenly, 10mL of commercially available polyamic acid PAA (K90) was added, and stirring was continued for 12h. The spinning solution was then placed in a refrigerator and allowed to stand for 12h.

[0040] (2) Preparation of the diaphragm:

[0041] The prepared spinning solution was electrospun at an injection rate of 0.5 mL / min and a voltage of 14 kV, with the distance between the needle and the receiving device adjusted to 10 cm. The spun diaphragm was dried in an oven at 105 °C for 12 h, and then placed in a muffle furnace and heated to 250 °C at a rate of 1 °C / min and held for 1 h.

[0042] Example 4

[0043] This embodiment prepares a lithium-ion battery separator, and the preparation method is as follows:

[0044] (1) Preparation of spinning solution:

[0045] 2g of PVP (K90) and 1g of commercially available ZIF-8 nanoparticles with a particle size of about 40nm were added to 10mL of LDM solution under stirring. After mixing evenly, 10mL of PAA prepared in step (2) was added and stirring was continued for 12h. The spinning solution was then placed in a refrigerator and allowed to stand for 12h.

[0046] (2) Preparation of the diaphragm:

[0047] The prepared spinning solution was electrospun at an injection rate of 0.5 mL / min and a voltage of 10 kV, with the distance between the needle and the receiving device adjusted to 10 cm. The spun diaphragm was dried in an oven at 105 °C for 12 h, and then placed in a muffle furnace and heated to 250 °C at a rate of 1 °C / min and held for 1 h.

[0048] Example 5

[0049] This embodiment prepares a lithium-ion battery separator, and the preparation method is as follows:

[0050] (1) Preparation of spinning solution:

[0051] 2g of PVP (K90) and 1g of commercially available ZIF-8 nanoparticles with a particle size of approximately 40nm were added to 10mL of LDM solution under stirring. After mixing evenly, 10mL of commercially available polyamic acid (PAA) was added, and stirring was continued for 12h. The spinning solution was then placed in a refrigerator and allowed to stand for 12h.

[0052] (2) Preparation of the diaphragm:

[0053] The prepared spinning solution was electrospun at an injection rate of 0.5 mL / min and a voltage of 20 kV, with the distance between the needle and the receiving device adjusted to 10 cm. The spun diaphragm was dried in an oven at 105 °C for 12 h, and then placed in a muffle furnace and heated to 250 °C at a rate of 1 °C / min and held for 1 h.

[0054] Comparative Example 1

[0055] The difference between this comparative example and Example 1 is that the spinning solution consists of PAA and ZIF-8 and does not contain PVP; otherwise, it is the same as Example 1.

[0056] Comparative Example 2

[0057] The difference between this comparative example and Example 1 is that the spinning solution is composed of PAA and PVP and does not contain ZIF-8, while all other aspects are the same as in Example 1.

[0058] Experimental Example

[0059] (1) Porosity

[0060] Equipment: PMI water pressure gauge

[0061] Method: When water is used as the test solution, water is forced into the pores under pressure. The pressure corresponding to water forced into different pore sizes follows the Washburn equation, so a series of pore structure parameters can be calculated.

[0062] (2) Closed-cell temperature

[0063] Equipment: Netzsch thermomechanical analyzer

[0064] Method: Heating rate 3℃ / min, load 20mN, closed-cell temperature is the temperature at the deformation inflection point near the melting point.

[0065] (3) Acupuncture intensity

[0066] Equipment: KES-G5 pressure tester

[0067] Method: A Hall effect sensor is used for sensing and testing. The internal amplifier outputs a voltage value, which is converted into a numerical signal by an integrator, and the test value is displayed on the terminal.

[0068] (4) Thermal shrinkage

[0069] Equipment: Electric heating forced-air drying oven

[0070] Method: The diaphragm is reacted for a period of time under a set temperature condition. The difference in length between the transverse and longitudinal directions of the diaphragm is measured with a ruler, and the heat shrinkage ratio is calculated.

[0071] (5) Liquid absorption and retention rate

[0072] Equipment: Electronic balance

[0073] Method: The diaphragm was weighed on an electronic balance, and the initial weight was recorded as W1. It was then placed in a beaker containing electrolyte, completely submerged, and the beaker was sealed for 60 minutes. The soaked sample was then removed and weighed, and recorded as W2. The weighed sample was then allowed to stand in a fume hood for 60 minutes, and weighed again, recorded as W3. Liquid absorption rate = (W2 - W1) / W1 × 100%; Liquid retention rate = (W3 - W1) / W1 × 100%.

[0074] The membranes prepared in Examples 1-5 and Comparative Examples 1-2 were subjected to performance tests according to the provided test methods. The test results are shown in the table below:

[0075] Table 1. Diaphragm performance of Examples 1-5 and Comparative Examples 1-2

[0076]

[0077]

[0078] As can be seen from the data in the table, the lithium-ion battery separators prepared by electrospinning in Examples 1 to 5 of this invention have better porosity, closure temperature, and liquid absorption / retention rate than the separators prepared in Comparative Examples 1 to 2. In the presence of PVP, this invention achieves in-situ control of the microporous to microporous-mesoporous hierarchical structure, and the confinement effect between PVP and ZIF-8 improves the uniformity of the pores. The uniform pore size distribution avoids local overheating caused by uneven current density during use. The addition of nano-sized ZIF-8 particles also improves the wettability and mechanical strength of the separator.

[0079] Comparing Example 1 and Example 2, it was found that when the mass ratio of PVP to ZIF-8 was 2:1, the porosity of the membrane was 56%, which was better than 50% in Example 2. This indicates that with the increase of PVP, the reactive sites of PVP and ZIF-8 increased, and the hydrogen bonding effect was stronger. The needle penetration strength of the membrane increased from 533 gf to 552 gf with the increase of PVP, indicating that in addition to the better pore structure distribution, the membrane also has stronger mechanical strength.

[0080] Comparing Examples 2 and 3, it was found that when the ZIF-8 content was increased, the membrane porosity decreased from 50% to 47%, indicating that further increasing PVP and ZIF-8 did not improve the pore distribution but instead reduced the porosity. The needle-punching strength decreased slightly from 533 gf to 531 gf, but the membrane's liquid absorption and retention rates both improved. The liquid absorption rate increased from 79.1% to 81.2%, and the liquid retention rate increased from 64.7% to 69.9%. This indicates that the membrane performance is optimal within a certain range of PVP and ZIF-8 ratio, and the addition of ZIF-8 has a certain effect on improving the membrane's liquid absorption and retention performance.

[0081] Comparing Examples 1, 4, and 5, it was found that the voltage mainly affects the porosity and strength of the diaphragm. When the voltage is reduced from 14kV to 10kV, the electrospun fibers are coarser, and the needle punching strength increases from 552gf to 561gf. However, the porosity of the diaphragm decreases from 56% to 48%.

[0082] Comparing Example 1 with Comparative Examples 1 and 2, it was found that when neither PVP nor ZIF-8 was added, the membrane porosity was low, indicating that the confinement effect between PVP and ZIF-8 after pyrolysis significantly altered the pore distribution. A comparison of data from Example 1 and Comparative Example 1 revealed that the addition of ZIF-8 greatly improved the membrane's liquid absorption and retention properties.

[0083] Comparative examples and comparative examples show that by using polyamide as raw material and adjusting the pore structure by adding PVP and ZIF-8, the closed-cell temperature of the examples is reduced to below 130°C, which is better than that of the comparative examples. This indicates that the safety and flame retardant performance of the embodiments of the present invention are superior.

[0084] from Figure 2 As can be seen from the pore size distribution diagrams of the embodiments and Comparative Example 1, the pore size of the membrane in Comparative Example 1 is mainly distributed in the range of 29-31 nm, and also in the range of 25-38 nm. In contrast, the pore size of the membrane in Example 1 is mainly distributed in the range of 46-48 nm. This further illustrates that the confinement effect between PVP and ZIF-8 optimizes the pore size distribution, making the pore size distribution more uniform, reducing the collapse of the PVP skeleton, and thus increasing the pore size.

[0085] In summary, the diaphragm prepared under the formulation and process conditions of this invention has uniform pores, excellent mechanical strength, thermal stability and liquid absorption and retention performance, and the closure temperature can reach below 130℃. It has advantages such as high safety, flame retardancy, good electrical conductivity and excellent liquid absorption and retention performance.

[0086] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a lithium battery separator with uniform pore distribution, characterized in that, The method includes the following steps: (1) Preparation of spinning solution: Polyvinylpyrrolidone (PVP) and ZIF-8 nanoparticles were added to a polar organic solvent and mixed evenly to prepare mixed solution 1. Polyamic acid was added and stirred for 8~24h to prepare spinning solution. (2) Preparation of ion battery coated separator: The spinning solution prepared in step (1) is electrospun to prepare a separator. After drying the separator, the temperature is increased at a rate of 1-5℃ / min to 230-300℃ and held for 1-2h.

2. The preparation method according to claim 1, characterized in that, The polar organic solvent in step (1) is N,N-dimethylformamide or N,N-dimethylacetamide.

3. The preparation method according to claim 1, characterized in that, Step (1) The spinning solution is used for subsequent operations after the air bubbles are eliminated.

4. The preparation method according to claim 3, characterized in that, Step (1) involves letting the mixture stand at a low temperature to eliminate air bubbles.

5. The preparation method according to claim 1, characterized in that, The volume / mass ratio of polyamic acid to PVP in step (1) is 10:1 to 2:

1.

6. The preparation method according to claim 1, characterized in that, The volume / mass ratio of polyamic acid to PVP in step (1) is 10:1, 10:3, or 5:

1.

7. The preparation method according to claim 1, characterized in that, In step (1), the mass ratio of polyvinylpyrrolidone (PVP) to ZIF-8 nanoparticles is 5:1 to 1:

1.

8. The preparation method according to claim 1, characterized in that, In step (1), the mass ratio of polyvinylpyrrolidone (PVP) to ZIF-8 nanoparticles is 3:1 to 1:

1.

9. The preparation method according to claim 1, characterized in that, In step (2), the sample feeding speed of electrospinning is 0.1-1 mL / h, the voltage is 10-20 KV, and the receiving distance is 10-20 cm.

10. A lithium battery separator with uniform pore distribution, characterized in that, The lithium battery separator with uniform pore distribution is prepared by the preparation method described in claim 1.

11. A lithium battery, characterized in that, The lithium battery separator includes the lithium battery separator with uniform pore distribution as described in claim 10.

Citation Information

Patent Citations

  • Metal organic framework / fiber composite membrane, preparation method thereof and application

    CN110739431A

  • Preparation method of polyimide-based mixed matrix hollow fiber membrane

    CN112717711A